2022
DOI: 10.1021/acsami.2c17109
|View full text |Cite
|
Sign up to set email alerts
|

Multi-Scale Computer-Aided Design of Covalent Organic Frameworks for CO2 Capture in Wet Flue Gas

Abstract: Discovery of remarkable porous materials for CO2 capture from wet flue gas is of great significance to reduce the CO2 emissions, but elucidating the most critical structure features for boosting CO2 capture capabilities remains a great challenge. Here, machine-learning-assisted Monte Carlo computational screening on 516 experimental covalent organic frameworks (COFs) identifies the superior secondary building units (SBUs) for wet flue gas separation using COFs, which are tetraphenylporphyrin units for boosting… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 57 publications
(83 reference statements)
0
6
0
Order By: Relevance
“…Function-oriented material synthesis strategies start with the prospective function rather than structure, harnessing the brainpower of chemists and the power of computers (such as data mining and machine learning) to create new structures with the desired functions . In view of their well-defined structures, COFs offer a unique opportunity to establish structure–property correlations and develop purposeful structural design for obtaining the desired functionality prior to material synthesis . MCRs are an excellent choice for achieving the function-oriented synthesis of COFs because of their potential to integrate three or more functional blocks capable of conferring unexpected properties and functions on COFs through synergistic interactions in addition to providing their functions independently.…”
Section: Summary and Further Challengesmentioning
confidence: 99%
“…Function-oriented material synthesis strategies start with the prospective function rather than structure, harnessing the brainpower of chemists and the power of computers (such as data mining and machine learning) to create new structures with the desired functions . In view of their well-defined structures, COFs offer a unique opportunity to establish structure–property correlations and develop purposeful structural design for obtaining the desired functionality prior to material synthesis . MCRs are an excellent choice for achieving the function-oriented synthesis of COFs because of their potential to integrate three or more functional blocks capable of conferring unexpected properties and functions on COFs through synergistic interactions in addition to providing their functions independently.…”
Section: Summary and Further Challengesmentioning
confidence: 99%
“…Modified with permission. 155 Copyright 2022, American Chemical Society. (e) High-performance COFs for heating, cooling and ice-making were identified through high-throughput computational screening based on large classical Monte Carlo simulations in ML.…”
Section: Selection Of Materials Descriptors the Choice Of Descriptors...mentioning
confidence: 99%
“…. Typically used solid sorbents like zeolites and porous carbons did not fulfill all requirements due to their low working capacities and/or low CO 2 /H 2 selectivity. Various porous materials with a good CO 2 adsorption capacity at low pressure as well as high pressure, such as metal organic frameworks, porous organic polymers, and covalent organic frameworks, have been used. However, to the best of our knowledge, most of these porous materials were studied for postcombustion CO 2 , and only few studies were reported on precombustion CO 2 capture, i.e., high-pressure CO 2 uptake. , The stored CO 2 can be reduced to value-added chemicals like methanol, formic acid, and so forth through high-pressure hydrogenation …”
Section: Introductionmentioning
confidence: 99%